Economic impacts of EU clean air policies assessed in a CGE framework. Issue 55 (January 2016) - Vrontisi, Zoi; Abrell, Jan; Neuwahl, Frederik; Saveyn, Bert; Wagner, Fabian
Abstract: This paper assesses the macroeconomic and sectoral impacts of the "Clean Air Policy Package" proposed by the European Commission in December 2013. The analysis incorporates both the expenditures necessary to implement the policy by 2030 and the resulting positive feedback effects on human health and crop production. A decomposition analysis identifies the important drivers of the macroeconomic impacts. We show that while expenditure on pollution abatement is a cost for the abating sectors, it also generates an increased demand for the sectors that produce the goods required for pollution abatement. Moreover, we find that positive feedback effects, particularly those related to health can offset the resource costs associated to the clean air policy and result in positive macroeconomic impacts for the economy of the European Union.